AKTIVITAS AKTIVITAS ANTIDIABETES EKSTRAK ETANOL DAUN BELIMBING BESI (Averhhoa carrambola) PADA MENCIT (Mus musculus) - WIDI YANTHI, NI PUTU SRI PUSPITA; Astiti, Ni Putu Adriani; Sudatri, Ni Wayan (SIMBIOSIS; Vol 9 No 2 (2021)DO - 10.24843/JSIMBIOSIS.2021.v09.i02.p02, 2021)
Many antioxidant compounds, flavonoids, and saponins are contained in starfruit leaves (Averrhoa carambola). The purpose of this study was to determine the antidiabetic activity of star fruit extract in mice. This study used a completely randomized design (CRD) with 6 treatments, namely P1 (aquadest without alloxan) as a negative control, P2 (aquadest with alloxan) as a positive control, P3 (metformin 500 mg / kgBB), P4 (alloxan + ethanol extract of star fruit leaves. 100 mg / kgBB), P5 (alloxan + ethanol extract of star fruit leaves 150 mg / kgBB), P6 (alloxan + ethanol extract of star fruit leaves 200 mg / kgBB). The starfruit leaf extract was made using the maceration method. In order for experimental animals to become diabetic, alloxan is used at a dose of 120 mg / kgBW which is injected intramuscularly into the thigh muscles. After the experimental animals were diabetic, We were given ethanol extract of starfruit leaves according to the experimental design, starting from day 7 th to day 21 st . Blood glucose levels are measured with a glucometer every week. The results showed that the best decrease in blood glucose levels occurred in the first week and the second week. In the first week, the metformin treatment was able to reduce blood glucose by 88.4%, while the ethanol extract treatment of star fruit leaves at a dose of 200 mg / kg BW was able to reduce blood glucose levels by 60%. The ethanol extract of star fruit leaves has antidiabetic activity. Keywords: mice, diabetes mellitus, blood glucose, starfruit leaves.